The Effect of Partial Defoliation on Quality Characteristics of Vitis vinifera L. cv. Cabernet Sauvignon Grapes 1. Sugars, Acids and pH - Hunter, J.J.; de Villiers, Q.T.; Watts, J.E. (South African Journal of Enology and Viticulture, 2017)
The effect was studied of partial defoliation (33% and 66%) on the sugar and acid accumulation and pH in grapes of Vitis vinifera L. cv. Cabernet Sauvignon. Although the total soluble sugar (TSS) in grapes of partially defoliated vines was significantly higher than that of non-defoliated vines in some cases, no significant differences were generally found. No significant differences in total titratable acidity (TT A) were found between treatments. The timing of defoliation had no effect on TSS in grapes, whereas TT A tended to be higher the earlier partial defoliation was commenced. In general, 33 % and 66% defoliated vines respectively produced approximately 33 % and 200% more TSS and TT A in the fruit per cm2 leaf area than non-defoliated vines. No significant differences between defoliation treatments were found on a per gram dry berry mass or per berry basis for glucose and fructose or tartaric and malic acid. However, 66% defoliated vines had significantly less soluble solids in berries per shoot, which was probably caused by a lower total berry mass per shoot. Although no significant differences in sugar composition could be found between defoliation treatments, tartaric acid levels tended to be higher and malic acid levels lower as a result of partial defoliation. Partial defoliation had no effect on the accumulation patterns of sugars and acids. Glucose dominated in berries at veraison, with fructose dominating at ripeness. The highest total tartaric and malic acid concentrations occurred at pea size. Malic acid content decreased rapidly from veraison, whereas the decrease in tartaric acid was not pronounced. Must pH was not affected by partial defoliation. The results seem to suggest that the general metabolism of vines was favourably changed by partial defoliation, mainly in terms of a more favourable source: sink ratio, more efficient photosynthesis, and an improved canopy microclimate.